BRITISH WOMEN WRITERS - Akramova Gulira'no Akmal qizi; Khamitov Eldor Erkin ògli (TADQIQOTLAR.UZ, 2024)
British women writers have made significant contributions to literature throughout history, spanning various genres and styles. From the early works of Jane Austen and the Brontë sisters to contemporary authors like Zadie Smith and J.K. Rowling, these writers have shaped literary landscapes and influenced generations of readers worldwide. This abstract aims to explore the diverse voices and themes present in the works of British women writers, highlighting their impact on literature and society. Through an examination of key works and critical analysis, this study seeks to illuminate the rich and complex narratives crafted by these writers, emphasizing their cultural significance and enduring relevance in the literary canon.